Prognosis by four-layer quasi-geostrophic model - MUKERJI, T. K.; DATTA, R. K. (MAUSAM, 1973)
Results of experiments in forecasting the heights of 850, 700, 500 and 300-mb levels 24 hours in advance, using a four-layer quasi-geostrophic model are presented here. As a first step, the vertical velocities of surface and 200-mb level have been assumed to be zero. The static stability parameter is computed from known values of temperatures and pressures. The area covered for the study has been made large, so as to avoid the effect of constant values at the boundaries on the forecast for Indian areas.